Fluidized Bed Reactor Type : Reactor Design for Biodiesel Production from SoyBean Oil Using MgO Catalyst - Fitri Febriyanti; Irine Sofianty; Adani Ghina Puspita Sari; Rofi Fadilah Madani; Muhammad Roil Bilad; Asep Bayu Dani Nandiyanto (Journal of Earth Energy Science, Engineering, and Technology, 2022)
Biodiesel is one of the solutions to future energy problems. One of the abundant biodiesel raw materials in Indonesia is soybean. This study aims to optimize the yield of biodiesel made from soybean oil by selecting the reactor design. This research method uses literature study and thermodynamic calculations from the transesterification reaction of soybean oil and methanol using a MgO catalyst to determine which type of reactor optimizes biodiesel yield. The type of reactor that can help optimize the yield of MgO biodiesel catalyst is a fluidized bed reactor type with an exothermic reaction and a negative Hf value. There is a higher product concentration than the reaction concentration in the scene because the rate constant is higher than one (K > 1), i.e. 1.312. The results of this study are expected to provide information in optimizing the yield of biodiesel from soybean oil.